Performance of Empirical Research as a Method for Achieving Professional Students’ Competence: a Case Study of Teaching Sales Skills to Future Employees of the Beauty Industry - Szczechowicz, Bartosz; Kryczka, Małgorzata; Alejziak, Wiesław (Journal of Education, Health and Sport, 2023)
Introduction and purpose. Didactic methods are evolving, among others, in the direction of engaging students in performance of empirical research gives rise to, in the first place, the students’ active participation in the process of knowledge creation and improves their methodological expertise. This paper presents an outlook on the value of the students’ participation in empirical research as a possibility for developing their professional competence. Material and method. A case study concerning education of the future employees of the cosmetic industry via engagement of students majoring in “cosmetology” (as part of classes forming a part of the “Sales Techniques in Cosmetology” course taught at the University of Physical Education in Kraków) in the preparation and performance of empirical research was presented. In the first place, general information pertaining to the system of educating cosmetologists in Poland and at the university in question was discussed; this offered a background for illustrating the characteristics of the aforementioned subject, with a focus on the module of classes devoted to the preparation and performance of empirical research. In the second place, the process encompassing: (1) students’ engagement in the research preparation, (2) students’ engagement in the performance of research, (3) students’ engagement in the analysis and interpretation of research results and (4) actions taken to utilize the results of research for didactic purposes, was presented. Results and conclusions. Benefits resulting from the proposed formula of teaching the subject were listed, with simultaneous reference to the diversified level of engagement of the lecturer and the students in the performance of individual stages of the research process.